Gestational and congenital toxoplasmosis: an epidemiological profile of extreme poverty municipalities in Brazil - de Faria Santos, Ana Karollyna; Zannon, Allan Vagner Monteiro da Silva; Miyuki Kondo, Amanda; Leal Cordeiro Júnior, Carlos Wagner; Morais Degan, Caroline; Nunes de Moura , Francisca Jessika (Journal of Health & Biological Sciences, 2025)
Objective: to evaluate the epidemiological profile of gestational and congenital toxoplasmosis in extreme poverty municipalities in Brazil from 2019 to 2022. Methods: this is an ecological study based on secondary data from the Information Technology Department of the Unified Health System (DATASUS). Information was collected on the number of notified cases of gestational and congenital toxoplasmosis, considering extreme poverty municipalities as the place of residence. The variables evaluated were region and race for gestational toxoplasmosis, age group, schooling, congenital toxoplasmosis, and gender. Results: between 2019 and 2022, 6,895 new cases of Gestational Toxoplasmosis (GT) and 1,677 new cases of Congenital Toxoplasmosis (CT) were reported in extreme poverty municipalities in Brazil. In terms of the country’s regions, the highest number of cases was concentrated in the Northeast during the period analyzed. Regarding cases by race, black people were the only ones with a statistically significant upward trend in both diseases. Analyzing cases by sex in CT, there was a percentage increase in both sexes, but with high statistical significance in females. As for the age group in GT, women aged between 20 and 39 showed a significant upward trend. Conclusion: based on the analysis of the data, the absolute numbers point to a significant increase in cases, especially in 2022.